a^{3}+b^{3}=(a+b)(a^{2}+b^{2}-ab) Posted by Kanwar Preet(student)on 13/11/09 This conversation is already closed by Expert

a^{3}+b^{3}=(a+b)(a^{2}+b^{2}-ab) Posted by Kanwar Preet(student)on 13/11/09 This conversation is already closed by Expert

a^{3}+b^{3}=(a+b)(a^{2}+b^{2}-ab) Posted by Kanwar Preet(student)on 13/11/09 This conversation is already closed by Expert

please explain how a^{3}+b^{3}= (a+b)(a^{2}-ab+b^{2}) and a^{3}-b^{3}= (a-b)(a^{2}+ab+b^{2}) Posted by ranjit2me...(parent)on 14/4/11

please explain how a^{3}+b^{3}= (a+b)(a^{2}-ab+b^{2}) and a^{3}-b^{3}= (a-b)(a^{2}+ab+b^{2}) Posted by ranjit2me...(parent)on 14/4/11

please explain how a^{3}+b^{3}= (a+b)(a^{2}-ab+b^{2}) and a^{3}-b^{3}= (a-b)(a^{2}+ab+b^{2}) Posted by ranjit2me...(parent)on 14/4/11

hELLO Sir... a^{3}+b^{3} = (a+b)^{3}-3ab(a+b) >>>This one is the formula for Expanding only... a^{3}-b^{3} = (a-b)^{3}+3ab(a+b) AND a^{3}+b^{3} = (a+b) (a^{2}-ab+b^{2}) >>>This is the formula for FACTORISING.... a^{3}+b^{3} = (a-b) (a^{2}+ab+b^{2}) Posted by Shubhayan Chand...(student)on 21/8/11

hELLO Sir... a^{3}+b^{3} = (a+b)^{3}-3ab(a+b) >>>This one is the formula for Expanding only... a^{3}-b^{3} = (a-b)^{3}+3ab(a+b) AND a^{3}+b^{3} = (a+b) (a^{2}-ab+b^{2}) >>>This is the formula for FACTORISING.... a^{3}+b^{3} = (a-b) (a^{2}+ab+b^{2}) Posted by Shubhayan Chand...(student)on 21/8/11

hELLO Sir... a^{3}+b^{3} = (a+b)^{3}-3ab(a+b) >>>This one is the formula for Expanding only... a^{3}-b^{3} = (a-b)^{3}+3ab(a+b) AND a^{3}+b^{3} = (a+b) (a^{2}-ab+b^{2}) >>>This is the formula for FACTORISING.... a^{3}+b^{3} = (a-b) (a^{2}+ab+b^{2}) Posted by Shubhayan Chand...(student)on 21/8/11

a^{3} - b^{3 } = (a-b) (a^{ 2 }+ab+b^{2}) (multiply these to expression) =a^{3}+a^{2}b+ab^{2}-a^{ 2 }b+ab^{2}-b^{3} (+a^{2}b-a^{ 2 }b=0 +ab^{2}+ab^{2}= 0 )^{ } =a^{3}-b^{3} Posted by Pralish Kayasth...(student)on 14/6/12

a^{3} - b^{3 } = (a-b) (a^{ 2 }+ab+b^{2}) (multiply these to expression) =a^{3}+a^{2}b+ab^{2}-a^{ 2 }b+ab^{2}-b^{3} (+a^{2}b-a^{ 2 }b=0 +ab^{2}+ab^{2}= 0 )^{ } =a^{3}-b^{3} Posted by Pralish Kayasth...(student)on 14/6/12

a^{3} - b^{3 } = (a-b) (a^{ 2 }+ab+b^{2}) (multiply these to expression) =a^{3}+a^{2}b+ab^{2}-a^{ 2 }b+ab^{2}-b^{3} (+a^{2}b-a^{ 2 }b=0 +ab^{2}+ab^{2}= 0 )^{ } =a^{3}-b^{3} Posted by Pralish Kayasth...(student)on 14/6/12

HERE IS D ANS GIVEN BY MERITNATION EXPERT...!!! a^{3}+b^{3} = (a+b)^{3}-3ab(a+b) >>>This one is the formula for Expanding only... a^{3}-b^{3} = (a-b)^{3}+3ab(a+b) AND a^{3}+b^{3} = (a+b) (a^{2}-ab+b^{2}) >>>This is the formula for FACTORISING.... a^{3}+b^{3} = (a-b) (a^{2}+ab+b^{2}) Posted by Shivani(student)on 7/10/12

HERE IS D ANS GIVEN BY MERITNATION EXPERT...!!! a^{3}+b^{3} = (a+b)^{3}-3ab(a+b) >>>This one is the formula for Expanding only... a^{3}-b^{3} = (a-b)^{3}+3ab(a+b) AND a^{3}+b^{3} = (a+b) (a^{2}-ab+b^{2}) >>>This is the formula for FACTORISING.... a^{3}+b^{3} = (a-b) (a^{2}+ab+b^{2}) Posted by Shivani(student)on 7/10/12

HERE IS D ANS GIVEN BY MERITNATION EXPERT...!!! a^{3}+b^{3} = (a+b)^{3}-3ab(a+b) >>>This one is the formula for Expanding only... a^{3}-b^{3} = (a-b)^{3}+3ab(a+b) AND a^{3}+b^{3} = (a+b) (a^{2}-ab+b^{2}) >>>This is the formula for FACTORISING.... a^{3}+b^{3} = (a-b) (a^{2}+ab+b^{2}) Posted by Shivani(student)on 7/10/12